The unexemplary being. For a non-violent humanism - La Matina, Marcello (Scenari, 2023)
In this article I attempt to develop a small semiophilosophical theory of violence, moving from the hypothesis that the current spiral in which we are all enmeshed may be derived from a logical-semantic character, which is normally present as such in taxonomies of all kinds, but has developed anomalously in modern cultures. The exemplariness of individuals, so I hypothesize, would act as a divisive social marker, causing conflicts between individuals who are (or are supposed to be) differently qualified relative to the species to which they claim to belong. Violence toward some given conspecific individuals would be caused by those individuals who, from time to time, feel their representativeness qua “fair samples” (in the sense Nelson Goodman assigned to these expressions) to be threatened. Here then is where the unexemplary being – i.e., the being who renounces its claim to lawlikeness with respect to the species or to the characters of the hegemonic community – can become the pick to unlock a new ontology of the human and beyond.